Virtual Reality as a Context for Adaptation - Yarossi, Mathew; Mangalam, Madhur; Naufel, Stephanie; Tunik, Eugene (Frontiers in Virtual Reality, 2021)
The COVID-19 pandemic has accelerated interest in virtual reality (VR) for education, entertainment, telerehabilitation, and skills training. As the frequency and duration of VR engagement increases—the number of people in the United States using VR at least once per month is forecasted to exceed 95 million—it is critical to understand how VR engagement influences brain and behavior. Here, we evaluate neurophysiological effects of sensory conflicts induced by VR engagement and posit an intriguing hypothesis: the brain processes VR as a unique “context” leading to the formation and maintenance of independent sensorimotor representations. We discuss known VR-induced sensorimotor adaptations to illustrate how VR might manifest as a context for learning and how technological and human factors might mediate the context-dependency of sensorimotor representations learned in VR.